2022
DOI: 10.1038/s41598-022-24232-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-factor settlement prediction around foundation pit based on SSA-gradient descent model

Abstract: With the rise of machine learning, a lot of excellent algorithms are used for settlement prediction. Backpropagation (BP) and Elman are two typical algorithms based on gradient descent, but their performance is greatly affected by the random selection of initial weights and thresholds, so this paper chooses Sparrow Search Algorithm (SSA) to build joint model. Then, two sets of land subsidence monitoring data generated during the excavation of a foundation pit in South China are used for analysis and verificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There are also studies that have made significant contributions by using optimization techniques to improve soil quality (Yuan et al, 2024a(Yuan et al, , 2024b, 2023 [20][21][22]). Additionally, some scholars have addressed surface settlement control within the design parameter control of foundation pit supporting structures [7,[23][24][25][26][27][28][29]. Surface settlement can significantly affect nearby structures and infrastructure, making its control a vital aspect of foundation pit design.…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies that have made significant contributions by using optimization techniques to improve soil quality (Yuan et al, 2024a(Yuan et al, , 2024b, 2023 [20][21][22]). Additionally, some scholars have addressed surface settlement control within the design parameter control of foundation pit supporting structures [7,[23][24][25][26][27][28][29]. Surface settlement can significantly affect nearby structures and infrastructure, making its control a vital aspect of foundation pit design.…”
Section: Introductionmentioning
confidence: 99%
“…The BP model has strong abilities of information processing, self-learning, nonlinear mapping, error feedback adjustment, and fault tolerance 37 – 41 . However, BP model also has some disadvantages such as slow convergence speed, long training time, difficult in achieve the overall optimum, and its prediction performance greatly depends on the random selection of initial weights and thresholds 35 , 42 . And the BP model requires large quantity training data and the data need to be widely representative 34 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Li and Qiu 22 proposed an SSA-ELM model for predicting open-pit slope displacement and found that the prediction accuracy was higher than that of the BPNN model. Li et al 23 analyzed and compared the optimizing effects of three optimization algorithms, SSA, GA, and PSO, combined with BPNN prediction, and found that SSA had a higher optimization efficiency and could more accurately predict ground subsidence caused by excavation pits. Whereas, due to the drawbacks in population initialization, position update strategy, etc., SSA has the problems of weak global search ability, slow convergence speed, and easy fall into local optimality.…”
Section: Introductionmentioning
confidence: 99%